HUBUNGAN ANTARA KELELAHAN KERJA (BURNOUT) DENGAN PERSEPSI PERAWAT TERHADAP PELAYANAN KEPERAWATAN BERMUTU DI UNIT RAWAT INAP RSUD BALUNG â JEMBER - Istiaji, Erdi; Irawan, R. Surya (FKM - UNEJ, 2009)
Nurses perceptions of quality nursing service is the process of giving the impression of value or by a nurse in providing nursing services to patients in accordance with the standards and quality expected hospital. Fatigue of work (Burnout), is a kind of psychological stress syndrome consisting of emotional exhaustion, depersonalisation, and decreased achievement in itself, experienced by individuals who work to provide services for others. Burnout is a phenomenon more common in social work compared to other occupations, it is because workers have to interact directly with patients or clients, dealing with clients who do not cooperate, contact with suffering patients, and others. Examples include professions in this field one of them is a nurse. This research uses korelasional research approach. Population of the study subjects were all correlation nurses who served in the Inpatient Unit-Jember Balung hospitals totaling 58 people. Retrieving data using questionnaire instruments, and performed data analysis using computer assistance with SPSS 12.0 for windows, the first conducted test the validity and reliability of assumptions to measure the level of instrument accuracy and regularity. The results of the questionnaire was found that fatigue of work (Burnout) of the 36 items 28 items found valid with reliability index of r = 0.794 revealed reliable. While the questionnaire to the nurses perception of quality of nursing service there are 36 items 29 items are valid with reliability index of r = 0.947 revealed reliable. Furthermore the test for normality and linearity test showed a normal spreading data and linear correlation. Then in the hypothesis test obtained rxy = 0.301 and a significance level of p = 0.022, which means there is a significant relationship between work exhaustion (Burnout) the nurses perception of quality nursing service in hospitals inpatient units Balung-Jember. Keywords: Work Fatigue (Burnout), Nursing Services Quality